Factors associated with indeterminate QuantiFERON-TB Gold Plus Test results during the COVID-19 pandemic - Carla M. Román-Montes; Karla M. Tamez-Torres; Guillermo A. Guaracha-Basañez; Alberto Ordinola-Navarro; Marco Antonio Ortiz-Bustamante; Sandra Rajme-López; Bernardo A. Martínez-Guerra; Anabel Ordaz-Vázquez; José Sifuentes-Osornio; Alfredo Ponce-de-León; Fernanda González-Lara; Miriam Bobadilla-Del-Valle (PLoS ONE, 2025)
Objective Indeterminate QuantiFERON (QFT) results challenge clinical decision-making and often necessitate repeat testing. This study aimed to assess the prevalence of indeterminate QFT results and identify associated factors. Method We compared patients with indeterminate QFT results to a 1:1 randomly selected sample of patients with determinate results from a tertiary care center in Mexico City between March 2020 and December 2022. Results Among 4,557 QFT®-Plus tests performed during the study period, 10% yielded indeterminate results. A total of 352 cases with indeterminate results and 352 with determinate results were analyzed. In 96% of cases, indeterminate results were attributed to a low mitogen response. No significant differences were observed in age, sex, or comorbidities between groups. Multiple regression analysis identified the following factors as significantly associated with an indeterminate QFT®-Plus result: severe COVID-19 (OR 3.9, 95% CI 2.5–6.2, p < 0.001), pharmacological immunosuppression (OR 1.7, 95% CI 1.2–2.4, p = 0.004), severe lymphopenia (OR 1.7, 95% CI 1.1–2.7, p = 0.02), anemia (OR 1.9, 95% CI 1.3–2.8, p = 0.001) and hospitalization (non–COVID–19) (OR 3.9, 95% CI 2.6–5.9, p < 0.001). Conclusion The prevalence of indeterminate QFT®-Plus test results was 10%, which is significant, particularly among patients with COVID-19. Indeterminate results were linked to immunosuppression and markers of disease severity. These findings suggest that it may be advisable to postpone QFT®-Plus testing until the clinical condition of patients improves.